2012
DOI: 10.1111/j.1469-0691.2011.03757.x
|View full text |Cite
|
Sign up to set email alerts
|

Pneumonia treated in the internal medicine department: focus on healthcare-associated pneumonia

Abstract: Patients with pneumonia treated in the internal medicine department (IMD) are often at risk of healthcare-associated pneumonia (HCAP). The importance of HCAP is controversial. We invited physicians from 72 IMDs to report on all patients with pneumonia hospitalized in their department during 2 weeks (one each in January and June 2010) to compare HCAP with community-acquired pneumonia (CAP) and hospital-acquired pneumonia (HAP). We analysed 1002 episodes of pneumonia: 58.9% were CAP, 30.6% were HCAP and 10.4% we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
43
2
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 29 publications
4
43
2
7
Order By: Relevance
“…pneumoniae was the most frequent pathogen of HCAP, and the frequency of atypical pathogens was 9.0 , results compatible with those of previous reports 3,4,[9][10][11][12] . Although the frequency of atypical pathogens was lower in HCAP than in CAP, the 9.0 incidence of atypical pathogens should not be ignored.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…pneumoniae was the most frequent pathogen of HCAP, and the frequency of atypical pathogens was 9.0 , results compatible with those of previous reports 3,4,[9][10][11][12] . Although the frequency of atypical pathogens was lower in HCAP than in CAP, the 9.0 incidence of atypical pathogens should not be ignored.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, urinary antigen tests, serological analysis, and RIDT were also used in the etiological diagnosis, with cases of unknown etiology also included. More recent studies have revealed that the most frequent pathogen is S. pneumoniae, and atypical pathogens have been detected in 0.7 to 16.1 of cases 3,4,[9][10][11][12] . In the present study, S.…”
Section: Discussionmentioning
confidence: 99%
“…66 Spanish hospitals found similar case-fatality rates for HCAP as well as high rates of infection with MRSA and Pseudomonas sp. 17 Both studies confirmed the need to differentiate HCAP from CAP in prescribing guidelines. In contrast, a more recent study from the United Kingdom' 6 found that although HCAP patients had a 30-day mortality rate more than twice that of CAP patients, after adjustment for baseline pneumonia severity index, comorbidities, and antimicrobial therapy, the odds of mortality with HCAP fell to 1.29 and were no longer significant.…”
Section: Discussionmentioning
confidence: 70%
“…While several studies on adherence to guidelines of empirical antibiotic therapy for CAP have been conducted in medical wards and intensive care units [6,[13][14][15], a relatively small number of studies have investigated adherence in patients with healthcare-associated pneumonias such as HAP or HCAP [7,[16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%